2018
DOI: 10.1080/08998280.2017.1400300
|View full text |Cite
|
Sign up to set email alerts
|

Chronic neutrophilic leukemia

Abstract: Chronic neutrophilic leukemia is a rare myeloproliferative disorder characterized by a sustained peripheral blood neutrophilia, absence of the BCR/ABL oncoprotein, bone marrow hypercellularity with less than 5% myeloblasts and normal neutrophil maturation, and no dysplasia. This leukemia has been associated with mutations in the colony-stimulating factor 3 receptor that may activate this receptor, leading to the proliferation of neutrophils that are the hallmark of chronic neutrophilic leukemia. We present a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…As shown in Table 1, two CNL‐MGUS patients with SETBP1 mutations reported in case 4 and case 5 all had blastic evolution during follow‐up treatment with hydroxyurea and died soon after 4 . After 1 month of ruxolitinib treatment for case 7, repeat NGS suggested clonal evolution by new mutations for SRSF2 and RUNX1 detected, and two previously mutated genes ( CSF3R and SETBP1 ) disappeared 6 …”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…As shown in Table 1, two CNL‐MGUS patients with SETBP1 mutations reported in case 4 and case 5 all had blastic evolution during follow‐up treatment with hydroxyurea and died soon after 4 . After 1 month of ruxolitinib treatment for case 7, repeat NGS suggested clonal evolution by new mutations for SRSF2 and RUNX1 detected, and two previously mutated genes ( CSF3R and SETBP1 ) disappeared 6 …”
Section: Discussionmentioning
confidence: 91%
“…23 However, a meta-analysis that included 3 reports totaling 56 cases of CNL indicated that the SETBP1 mutation had no unfavorable effect on the prognosis of CNL. 30 As shown in acquired new gene mutations during the follow-up process, 6 and the 2 patients reported in cases 4 and 5 had blastic evolution during the treatment process, 4 indicating that CNL-PCD will undergo clonal evolution or blastic evolution. However, whether CNL-PCD is the same as isolated CNL with similarities in clonal evolution or blastic evolution needs to be expanded for further analysis.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations